2013
DOI: 10.1074/jbc.m112.425975
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 Inositol (1,4,5)-Trisphosphate Receptor Activates Ryanodine Receptor 1 to Mediate Calcium Spark Signaling in Adult Mammalian Skeletal Muscle

Abstract: Background: Osmotic stress triggers RyR-mediated Ca 2ϩ sparks that are spatially confined at the periphery of muscle fibers. Results: Pharmacological intervention of IP 3 production and genetic ablation of IP 3 R suppressed RyR-mediated Ca 2ϩ sparks. Conclusion: Activation of the type 1 IP 3 R is necessary to induce Ca 2ϩ sparks. Significance: This work highlights a potential interaction between IP 3 R and RyR in mediating Ca 2ϩ signaling in adult skeletal muscle fibers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 38 publications
2
24
0
Order By: Relevance
“…It is also worth noting that blocking RyR channels with DANT also partially inhibited the rescue of DA neurons by OXB, suggesting that ER calcium released via IP 3 R might also serve to activate RyR through a calcium-induced calcium release mechanism. Consistent with this possibility, a cross-talk between IP 3 R and RyR has already been described in skeletal muscle cells (Tjondrokoesoemo et al, 2013). Present data are also globally consistent with previous studies showing that ER calcium pools may be crucial for the control of DA cell survival in a state of chronic neurodegeneration (Cali et al, 2012;Michel et al, 2013).…”
Section: Survival Promotion Of Dopamine Neurons By Orexinsupporting
confidence: 81%
“…It is also worth noting that blocking RyR channels with DANT also partially inhibited the rescue of DA neurons by OXB, suggesting that ER calcium released via IP 3 R might also serve to activate RyR through a calcium-induced calcium release mechanism. Consistent with this possibility, a cross-talk between IP 3 R and RyR has already been described in skeletal muscle cells (Tjondrokoesoemo et al, 2013). Present data are also globally consistent with previous studies showing that ER calcium pools may be crucial for the control of DA cell survival in a state of chronic neurodegeneration (Cali et al, 2012;Michel et al, 2013).…”
Section: Survival Promotion Of Dopamine Neurons By Orexinsupporting
confidence: 81%
“…In addition, recent findings show that IP 3 signaling is less prominent in adult skeletal muscle fibers compared to immature myotubes (38). However, osmotic stress transiently triggers prominent peripheral Ca 2þ sparks that occur as a result of cross talk between type I IP 3 receptors (IP 3 Rs) and type I RyRs (39). Given the peripheral localization of osmotic shock-induced Ca 2þ sparks, it is plausible that the IP 3 Rs are actually nuclear receptors (40).…”
Section: Introductionmentioning
confidence: 97%
“…entry (Launikonis et al 2003) and a role in voltage-activated and voltage-independent cytosolic Ca 2? signals (Casas et al 2010;Tjondrokoesoemo et al 2013 respectively).…”
Section: Introductionmentioning
confidence: 98%
“…sparks near the periphery of the muscle fibers. Tjondrokoesoemo et al (2013) reported that osmoticstress induced Ca 2? sparks were suppressed by the inhibition of either PLC or Ins(1,4,5)P 3 receptors and were facilitated following photolysis of caged Ins(1,4,5)P 3 .…”
Section: Introductionmentioning
confidence: 99%